Legislative Governance in People's Mining Policy: Balancing Economic, Environmental, and Social Dimensions in Bone Bolango - Yeyen Saptiani Sidiki; Asna Aneta (Departemen Administrasi Publik, Universitas Diponegoro, 2026)
This study examines the governance of artisanal and small-scale mining (ASM) in Bone Bolango Regency, with a particular focus on the role of the Regional House of Representatives (DPRD) in balancing economic, environmental, and social interests. Although the contribution of ASM to the Gross Regional Domestic Product (GRDP) is relatively small, the sector serves as a primary or supplementary livelihood for more than 4,000 households, creating a high level of microeconomic dependency. The research employs a systematic literature review, analysis of government data, official statistics, and local media reports to map economic dynamics, ecological risks, and social vulnerabilities. The findings reveal that the DPRD tends to align with the aspirations of the majority of miners, while environmental concerns and the protection of vulnerable groups—such as women, children, and indigenous communities—receive limited attention. Unregulated mining practices generate significant ecological risks, including mercury contamination and landslides, as well as social conflicts related to land access and ownership. The study concludes that more adaptive and inclusive legislative strategies are needed, encompassing the strengthening of deliberative forums, participatory monitoring, ecological risk zoning, and compensation mechanisms for affected groups. Through such approaches, ASM can continue to sustain community-level microeconomies while minimizing ecological and social risks, thereby achieving a balance between economic growth, environmental sustainability, and social justice.